“A Life More Ordinary” Processes of 5-Year Recovery From Substance Abuse. Experiences of 30 Recovered Service Users - Bjornestad, Jone; Svendsen, Thomas Solgaard; Slyngstad, Tale Ekeroth; Erga, Aleksander H.; McKay, James R.; Nesvåg, Sverre; Skaalevik, Alexander Waagan; Veseth, Marius; Moltu, Christian (Frontiers in Psychiatry, 2019)
Background: Studies investigating the subjective experiences of long-term recovery from substance use disorder are scarce. Particularly, functional and social factors have received little attention. Objectives: To investigate what long-term recovered service users found to build recovery from substance use disorder. Material and Methods: The study was designed as a phenomenological investigation subjected to thematic analysis. We interviewed 30 long-term recovered adult service users. Results: Our thematic analysis resulted in five themes and several subthemes: 1) paranoia, ambivalence and drug cravings: extreme barriers to ending use; 2) submitting to treatment: a struggle to balance rigid treatment structures with a need for autonomy; 3) surrendering to trust and love: building a whole person; 4) a life more ordinary: surrendering to mainstream social responsibilities; and 5) taking on personal responsibility and gaining autonomy: it has to be me, it cannot be you. Conclusions: Our study sample described long-term recovery as a developmental process from dependency and reactivity to personal autonomy and self-agency. The flux of surrendering to and differentiating from authority appeared to be a driving force in recovery progression. Participants called for treatment to focus on early social readjustment.